Identification of an Identical de Novo SCAMP5 Missense Variant in Four Unrelated Patients With Seizures and Severe Neurodevelopmental Delay - Jiao, Xianru; Morleo, Manuela; Nigro, Vincenzo; Torella, Annalaura; D’Arrigo, Stefano; Ciaccio, Claudia; Pantaleoni, Chiara; Gong, Pan; Grand, Katheryn; Sanchez-Lara, Pedro A.; Krier, Joel; Fieg, Elizabeth; et al. (Frontiers in Pharmacology, 2020)
Objective: To establish and broaden the phenotypic spectrum of secretory carrier membrane protein (SCAMP5) associated with epilepsy and neurodevelopmental delay. Methods: A Chinese patient was identified at the First Hospital of Peking University, and the three unrelated patients were recruited from two different countries (Italy and United States) through GeneMatcher. SCAMP5 pathogenic variants were identified by whole exome sequencing; clinical data of the patients were retrospectively collected and analyzed. Result: The onset age of seizures was ranged from 6 to 15 months. Patients had different types of seizures, including focal seizures, generalized tonic-clonic seizures and tonic seizure. One patient showed typical autism spectrum disorder (ASD) symptoms. Electroencephalogram (EEG) findings presented as focal or multifocal discharges, sometimes spreading to generalization. Brain magnetic resonance imaging (MRI) abnormalities were present in each patient. Severe intellectual disability and language and motor developmental disorders were found in our patients, with all patients having poor language development and were nonverbal at last follow-up. All but one of the patients could walk independently in childhood, but the ability to walk independently in one patient had deteriorated with age. All patients had abnormal neurological exam findings, mostly signs of extrapyramidal system involvement. Dysmorphic features were found in 2/4 patients, mainly in the face and trunk. All four unrelated patients were found to have the same heterozygous pathogenic SCAMP5 de novo variant (p. Gly180Trp). Conclusion: Epilepsy, severe developmental delay, abnormal neurological exam findings, with or without ASD or variably dysmorphic features and were common in patients with SCAMP5 variant. The onset time and type of seizure varied greatly. The EEG and brain MRI findings were not consistent, but diverse and nonspecific. The motor ability of patients with heterozygous SCAMP5 variant might have a regressive course; language development was more severely affected.